Escrituras femininas de l’après 68 : Rosalina Ròcha - Maria-Joana Verny (Revue des Langues Romanes)
The years after 1968 saw the flowering of a new Occitan literary creation, accompanied by the Nouvelle chanson occitane - born in 1965 with Gui Broglia's interpretations of Robert Lafont. A militant theatre was also born. In these forms of expression, women's voices were heard, albeit in a minority. This article focuses on one of them, Roseline Roche, author of several collections, first of poetry and then of prose, and talented editor of the literary review Jorn, before taking refuge in silence, discouraged by the lack of criticism of her texts. A woman's voice, evoking dramas that are often invisible behind the daily life of women, children, adolescents and adults.